The Effects of Forest Management Activities on Genetic Diversity of Forest Trees - Subash Gautam; Sachin Timilsina; Manish Shrestha (CV. Literasi Indonesia, 2021)
Genetic diversity helps to survive forest trees in several environmental changes and disease conditions. Different forest management activities such as harvesting, thinning, natural or artificial regeneration, seedlings or coppice forests, fragmentation, and overexploitation have a tremendous influence on the genetic diversity and population structure of forest trees. This paper aimed to review the impacts of these activities on the genetic diversity of forest trees. For this, we reviewed several scientific literature related to forest management practices that affect genetic diversity. Altogether,75 papers were reviewed, interpreted, and evaluated to prepare our final manuscript. The result of this study recommends that the level of genetic impacts varies with management activities, stand structure as well as species characteristics. There is very limited information about the impacts of forest management practices on the genetic diversity of forest trees since it is only focused on the growth of stands. The field research activities for species-specific must be executed considering ecological and reproductive parameters to assure sustainable forest ecosystems. Hence, this review will be beneficial for forest conservationists, researchers, and managers for the management of forests through better forest management activities preserving a genetic pool of the forest trees, and sustainable utilization of forest products.